2021
DOI: 10.1021/acs.jpcb.1c00771
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Helix-Turn-Helix Motif of Transcription Factors MarA and Rob Drives DNA Recognition

Abstract: DNA-binding proteins play an important role in gene regulation and cellular function. The transcription factors MarA and Rob are two homologous members of the AraC/XylS family that regulate multidrug resistance. They share a common DNA-binding domain, and Rob possesses an additional C-terminal domain that permits binding of low-molecular weight effectors. Both proteins possess two helix-turn-helix (HTH) motifs capable of binding DNA; however, while MarA interacts with its promoter through both HTH-motifs, prio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 98 publications
3
16
0
Order By: Relevance
“…In good agreement with these observations, substitutions of the above key residues involved in Rob-DNA interactions (Y33A, Q39A and R90A) and acidic loop (K190A, del187-193) confer significant defects in transcription activation activities verified by our Mango-based transcription assay (Figure 4F ) and Rob-TAC formation activities ( Supplementary Figure S10A and B ), suggesting the importance of their functions. This is in accordance with the recently reported molecular dynamics simulation experiment which proposed that the acidic loop of Rob might facilitate interconversion between the distinct DNA binding modes observed in MarA and Rob ( 52 ). These evidences reveal the necessity and accessory role of the acidic loop for Rob-dependent transcription activation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In good agreement with these observations, substitutions of the above key residues involved in Rob-DNA interactions (Y33A, Q39A and R90A) and acidic loop (K190A, del187-193) confer significant defects in transcription activation activities verified by our Mango-based transcription assay (Figure 4F ) and Rob-TAC formation activities ( Supplementary Figure S10A and B ), suggesting the importance of their functions. This is in accordance with the recently reported molecular dynamics simulation experiment which proposed that the acidic loop of Rob might facilitate interconversion between the distinct DNA binding modes observed in MarA and Rob ( 52 ). These evidences reveal the necessity and accessory role of the acidic loop for Rob-dependent transcription activation.…”
Section: Resultssupporting
confidence: 93%
“…Unlike MarA, which can insert its two conserved HTH motifs into the corresponding DNA major grooves of mar promoter and bends DNA by 35°, the co-crystal structure of Rob– micF showed that Rob could only insert helix α3 of HTH A into the A site of robbox , with helix α6 of HTH B contacting the phosphate backbone of B site, and thus rendering promoter DNA unbent ( Supplementary Figures S11A ) ( 30 ). However, some other in vivo and in vitro assays on Rob held different opinions ( 32 , 52 ) and it needs to be further clarified. Surprisingly, both helix α3 of HTH A and helix α6 of HTH B in Rob-TAC II insert into the DNA major grooves of robbox and make the DNA bent with an orientation similar to that of MarA (Figure 4A – D ; Supplementary Figures S11B ), revealing a general promoter remodeling mode for the AraC/XylS family transcription activators.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional molecular dynamics (cMD) simulations were performed following the same protocol as our prior study of MarA in complex with various DNA promoter sequences 33 . In brief, all simulations were performed using the Amber ff14SB force field 60 to describe MarA and Rob, the Parmbsc1 force field to describe the DNA 61 , and the CUDA version of the PMEMD module 62 of the AMBER 18 simulation package 63 .…”
Section: Methodsmentioning
confidence: 99%
“…Protein−ligand complex was prepared with the Protein Preparation Wizard to fix protonation states of amino acids, add hydrogens, and fix missing side-chain atoms, where we selected the most likely ionization state as proposed by the software, and the structures were minimized. Currently, DNA-binding interactions associated with the carboxy-terminal domain (CTD) of other AraClike proteins' CTD have been inferred from static models based on similar MarA and Rob proteins [66][67][68][69] . However, there are no structural studies focused on the full length HilD protein regarding how the amino-terminal domain (NTD) and CTD interact with each other, and how potential ligands interfere with this geometry.…”
Section: Molecular Modelling For Hild's Binding Site Prediction and C...mentioning
confidence: 99%